Drivers of Online Skincare Purchase Decisions among Young Consumers in Surabaya - Yandri Samuel Augusteyn; Sardina Sobeukum; Merlin Kristen Ratu Elo (School of Business, IPB University (SB-IPB), 2026)
Background: Although environmental awareness is on the rise, the gap between attitudes and eco-friendly purchasing behavior remains a challenge in the online shopping ecosystem. In Surabaya, this issue is particularly relevant given the urgency of managing urban waste, including single-use plastic waste that can originate from various consumer product packaging, such as skincare products.Purpose: This study aims to analyze the simultaneous and partial effects of Eco-Friendly Product Innovation, Eco-Friendly Brand Image, and Eco-Friendly Marketing on online purchasing decisions for skincare products among Generation Y and Z in Surabaya. The Stimulus-Organism-Response (S-O-R) framework was used as a conceptual lens to explain the relationships among the variables.Design/methodology/approach: This explanatory quantitative study involved 203 active respondents in Surabaya selected through purposive sampling. Data were collected via an online questionnaire, while the quality of the instrument was tested through validity and reliability tests. Data were analyzed using multiple linear regression with the aid of SPSS version 26.Findings/Results: The results of the study indicate that all variables simultaneously have a significant effect on purchasing decisions, with an R-squared value of 0.721. This means that these three variables account for 72.1% of the variation in purchasing decisions. Partially, Eco-Friendly Marketing is the most dominant predictor with a t-value of 19.144, followed by Eco-Friendly Product Innovation with a t-value of 4.618 and Eco-Friendly Brand Image with a t-value of 2.837. These findings indicate that the transparency of educational information in marketing plays a crucial role in influencing the purchasing decisions of young consumers in the digital market.Conclusion: This study shows that eco-friendly marketing, product innovation, and eco-friendly brand image play a role in shaping young consumers’ purchasing decisions when buying skincare products online. Companies are advised to enhance the transparency of sustainability information and maintain consistency in their eco-friendly claims to reduce consumer skepticism regarding greenwashing practices.Originality/Value (State of the art): This study makes an empirical contribution to the study of eco-friendly consumer behavior in the context of online purchases of skincare products in Surabaya. The results of this study show that eco-friendly marketing, product innovation, and brand image can be important factors in understanding the purchasing decisions of young consumers in the local digital market. Keywords: green brand image, green marketing, green product innovation, purchase decision